Digital Pedagogy in Action: Enhancing Critical Thinking through YouTube in Islamic Religious Education - Abil Fida Muhammad Qois Al Hadi; Anggraini, Fadhilla Nangroe; Mutohharun Jinan; Muh. Nur Rochim Maksum; Rabi’atuladawiyah Binti Jamaludin (Tadibia Islamika: Journal of Holistic Islamic Education, 2025)
The integration of information technology in education has become increasingly critical in the digital era, particularly for enhancing pedagogical effectiveness. YouTube, as the world's most prominent video-sharing platform, has emerged as a significant educational tool across diverse disciplines, including Islamic Religious Education (PAI). Despite providing global access to extensive educational content, substantial challenges persist in its pedagogical implementation, particularly regarding inadequate digital literacy among Indonesian secondary school students. This study investigates the utilization of YouTube as an instructional medium for developing critical thinking skills in PAI learning contexts. Employing a qualitative case study design, this research collected data through semi-structured interviews, classroom observations, and document analysis involving PAI teachers and students from multiple Indonesian high schools. Findings reveal that while YouTube offers diverse educational content with potential to foster critical thinking development, the majority of students engage in passive consumption patterns, lacking analytical depth in processing presented material. Although interactive features, including comment sections, content sharing, and subscription mechanisms, demonstrate potential for promoting deeper cognitive engagement, their educational benefits remain underutilized. The study identifies two principal barriers to effective YouTube integration: insufficient student digital literacy and inconsistent content quality. These findings contribute to the emerging scholarship on digital platform utilization in religious education and provide empirical evidence for enhancing critical thinking pedagogy through technology-mediated instruction in Indonesian educational contexts.